2017
DOI: 10.1371/journal.pone.0177387
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the PI3K/Akt pathway during decidualization of endometrial stromal cells

Abstract: Infertility is constantly increasing in Canada, where 16% of Canadian couples are experiencing difficulty conceiving. It is thought that infertility can emanate from the dysregulated communication between the embryo and the maternal endometrium. In order to allow for this window of implantation to be open at the right moment, endometrial stromal cells proliferate and differentiate by a mechanism called decidualization. Intracellular and molecular mechanisms involved in the regulation of apoptosis and cell prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 47 publications
2
38
0
Order By: Relevance
“…The underlying mechanism and factors responsible for the decrease of p-S473 AKT during decidualization in ESCs remains unknown. The decrease in AKT activity in decidualization is isoform specific and site specific and does not involve ubiquitin-proteasome degradation (Fabi et al 2017). Progesterone, which regulates the activation of AKT in many cell types and induces the decidualization of ESCs, may be involved.…”
Section: Figurementioning
confidence: 97%
“…The underlying mechanism and factors responsible for the decrease of p-S473 AKT during decidualization in ESCs remains unknown. The decrease in AKT activity in decidualization is isoform specific and site specific and does not involve ubiquitin-proteasome degradation (Fabi et al 2017). Progesterone, which regulates the activation of AKT in many cell types and induces the decidualization of ESCs, may be involved.…”
Section: Figurementioning
confidence: 97%
“…Indeed, the pathway resembles an interchange subway station serving additionally the decidualization and the implantation routes. One of the important functions of the pathway is to successfully inhibit Akt signaling during decidualization [ 40 ]. Indeed, recent studies on infertile women have reported that impaired Akt signaling during proliferation might contribute to endometrial ineptitude to promote relevant cascades en route to decidualization [ 41 ].…”
Section: Proliferation Route: Building the Functionalismentioning
confidence: 99%
“…Conversely, the other cAMP-induced factor, FOXO1, suppresses cyclin B1/2 and CDK1 [ 76 ]. Considering that the cAMP/PKA pathway is an inhibitor of the PI3K/Akt proliferative pathway, the complexity of cell cycle regulation during decidualization is highlighted [ 40 ]. An important role of cAMP in sensitizing endometrial cells to P4 is to prevent sumoylation of the PR by altering the expression of numerous small ubiquitin-like modifier (SUMO) enzymes [ 77 ].…”
Section: Decidualization Route: Priming the Endometrium For Implanmentioning
confidence: 99%
“…For example, KEGG annotation showed that cell junctions (focal adherens, adhesive, and tight junctions) and the PI3K–Akt signaling pathway were significantly enriched. The PI3K–Akt signaling pathway is associated with stromal cell decidualization (Z. Yang et al, ). Embryo implantation involves the events of trophocyte attachment and invasion or stoma cell migration, which may rely on cell junction changes between cell and cell or cell and matrix.…”
Section: Discussionmentioning
confidence: 99%